Wheelchair tennis, from health to competitive analysis: A narrative review - Sánchez-Pay, A.; Sanz-Rivas, D. (Journal of Human Sport & Exercise, 2021)
Objective: The purpose of this article is to analyse benefits of the playing wheelchair tennis in people with disabilities and to know some aspects that affect a player´s performance. Methods: Keyword search of Medline, SPORT Discus and Scholar Google databases was conducted to find relevant studies pertaining to: wheelchair tennis and adapted sports. The search was carried out from 1988 to February 2018. Also reference lists of articles obtained were manually searched for relevant literature. Narrative review methods were used to synthesise the data. Results: The psychology literature was limited, although wheelchair tennis seems to provide a reduction in depression and trait anxiety and an increase in vigour. Playing wheelchair tennis is sufficient to prevent the development of cardiovascular diseases, due the energy expenditure is comparable to the recommendations of the American College of Sports Medicine. Wheelchair mobility seems to be an important factor of success in WT, and the chair configuration affects the moving speed. Conclusions: Following the studies presented in this paper, we recommend that people with disabilities playing sport to improve their health condition. Also, coaches and fitness trainers can use the information provided within this study to adapt and improve the specific training programs for players.